Computer visualisation in urban planning of highway surroundings - Siewczyński, Borys (Journal of Civil Engineering and Management, 2004)
Computer visualisation is described as useful instrument, that enables to design urban (municipal) surroundings of highways and other main (supralocal) road communication lines in optimal way. Capabilities of visualisation techniques are presented by selected examples of spatial planning and urban spaces design. The presented examples show importance of urban space perception from viewpoint of road traffic participant. The paper also describes aesthetic issues concerning design of urban and suburban spaces, connected with elements of main transit roads, and their technical infrastructure. Some exemplary design processes of wide near‐by highway areas, using architectural and town planning methodology aided by computer visualisation are described too, as the significance of visual presentation quality is in close connection with specific planning tasks. Computer visualisation, visual information is shown as instruments that allow local communities to participate in design, spatial planning, and legislation.First Published Online: 14 Oct 2010